2019
DOI: 10.1085/jgp.201912358
|View full text |Cite
|
Sign up to set email alerts
|

Isolating a reverse-mode ATP synthase–dependent mechanism of mitoflash activation

Abstract: Wei-LaPierre and Dirksen discuss new work investigating the molecular events underlying mitoflash biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Indeed, phosphorylated lipids are critical regulators of mitochondrial functions and S1P is a potent lipid mediator that regulates various physiological processes as well as diverse mitochondrial functions such as mitochondrial respiration, ETC functioning, or mitochondrial-dependent cell death ( Hernández-Corbacho et al, 2017 ; Nielson and Rutter, 2018 ). Furthermore, it was reported that S1P interaction with Prohibitin 2 (PHB2) regulates ETC functioning and mitochondrial respiration ( Strub et al, 2011 ) and that a link between PHB2, ETC functioning and the activation of ‘mitoflashes’ ( Jian et al, 2017 ) exists, which are dynamic and transient uncouplings of mitochondrial respiration from ATP production that are partially dependent on the ‘reverse mode’ of the F O F 1 -ATPase ( Wei-LaPierre and Dirksen, 2019 ). Thus, it is possible that Lp Spl modulates mitochondrial S1P levels helping the induction of the ‘reverse mode’ of the mitochondrial F O F 1 -ATPase by involving PHB2, ETC complex assembly, or the generation of mitoflashes, a fascinating possibility that we will further investigate.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, phosphorylated lipids are critical regulators of mitochondrial functions and S1P is a potent lipid mediator that regulates various physiological processes as well as diverse mitochondrial functions such as mitochondrial respiration, ETC functioning, or mitochondrial-dependent cell death ( Hernández-Corbacho et al, 2017 ; Nielson and Rutter, 2018 ). Furthermore, it was reported that S1P interaction with Prohibitin 2 (PHB2) regulates ETC functioning and mitochondrial respiration ( Strub et al, 2011 ) and that a link between PHB2, ETC functioning and the activation of ‘mitoflashes’ ( Jian et al, 2017 ) exists, which are dynamic and transient uncouplings of mitochondrial respiration from ATP production that are partially dependent on the ‘reverse mode’ of the F O F 1 -ATPase ( Wei-LaPierre and Dirksen, 2019 ). Thus, it is possible that Lp Spl modulates mitochondrial S1P levels helping the induction of the ‘reverse mode’ of the mitochondrial F O F 1 -ATPase by involving PHB2, ETC complex assembly, or the generation of mitoflashes, a fascinating possibility that we will further investigate.…”
Section: Discussionmentioning
confidence: 99%